تحليل اقتصادي لاستجابة عرض محصول الحنطة في المنطقة الديمية باستخدام أنموذج التكامل المشترك وتصحيح الخطأ للمدة 2010-1960 (المجلة العراقية للعلوم الاقتصادية, 2018)
Wheat is considered as one of the most important cereal crops, and represents a world-wide peculiar issue. Therefore, most countries, including Iraq, endeavor to achieve the self-sufficiency from it. This study aimed to estimate wheat supply response in rained region in Iraq for the period 1960-2010 using cointegration and error correction model. To accomplish this aim, main factors influencing wheat acreage supply response were determined which include: wheat price, competing crop (barley), total product, crop price, rainfall, and production arisk. In order to avoid spurious regression problem, time series of the model variables were analyzed using ADF and KPSS tests. Results of these tests revealed that the time series were non-stationary in their levels, stationary in their first differences, and they were all cointegrated except the production risk and total product time series which were stationary in their levels. The tests also demonstrated a long run equilibrium relationship between wheat-cultivated area and its determinants. To estimate the short and long run determinants effects on wheat-cultivated area, the vector error correction model (VECM), was used , and the results revealed the significance of wheat price, barley price, and rainfall which represented about 66% of the change in wheat-cultivated area. In addition, there was ashort and long run relationship between wheat-cultivated area and its determinants. According to VECM results, the wheat-cultivated area is corrected from its disequilibrium in every previous period by -0.556 toward its equilibrium value. The speed of adjusting to equilibrium takes 1.79 years after the shock in the model which results from the change of one of the explanatory variables. Estimated elasticities indicate that price elasticities of wheat in relative to its price were 0.254 and 0.4608 in the short and long run respectively. Whereas, cross elasticities for wheat were -0.303 and 0.5987 in the short and long run respectively. Wheat supply elasticity in relation to the rainfall were 0.4502 in the short run and 0.6632 in the long run. As the elasticities values were less than one, the supply of this crop can be described as inelastic.Keywords: cointegration, error correction, supply response, time series.